3D printing construction and preparation method of vancomycin-loaded multi-level porous artificial bone scaffold model

Through 3D printing and freeze-drying technology, multi-stage pore artificial bone model is constructed, combining polycaprolactone and β-TCP outer layer with PCL/MC/VCM inner layer, solving the problems of low mechanical strength of bone repair materials and uncontrollable pore structure. , realizes bone tissue regeneration and drug sustained release, with excellent biocompatibility and clinical application prospects.

CN116392638BActive Publication Date: 2024-12-20TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310055976.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-16
Publication Date
2024-12-20
Estimated Expiration
2043-01-16

AI Technical Summary

Technical Problem

The existing bone repair materials have problems such as low mechanical strength, uncontrollable pore structure, high rejection, and high transplant difficulty, which is difficult to meet the mechanical strength requirements and pore structure requirements of bone repair sites.

Method used

Polycaprolactone (PCL)/β-tricalcium phosphate (β-TCP) outer porous scaffold and freeze-dried polycaprolactone (PCL)/mineralized bovine source type I collagen (MC) /Composite preparation of the inner porous scaffold of vancomycin (VCM) forms a multi-stage porous artificial bone model, which improves mechanical strength and drug sustained release performance through the combination of the outer layer and the inner layer.

Benefits of technology

It has achieved excellent mechanical strength and drug sustained release performance of multi-stage pore artificial bone stents, promoted bone tissue regeneration, reduced infection risk, met the demand for porosity and pore size of bone repair, and has good biocompatibility and clinical application potential. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116392638B_ABST
    Figure CN116392638B_ABST
Patent Text Reader

Abstract

The present invention discloses a 3D printing construction and preparation method of a vancomycin-loaded multi-level porous artificial bone scaffold model, which is a preparation method for constructing an artificial bone scaffold with a multi-level porous structure for infectious bone repair by 3D printing polycaprolactone (PCL) / β-tricalcium phosphate (β-TCP) to prepare an outer layer porous scaffold and a polycaprolactone (PCL) / mineralized bovine type I collagen (MC) / vancomycin hydrochloride (VCM) inner layer porous scaffold prepared by freeze drying (multi-level porous scaffold hereinafter referred to as PT-MCP-V), belonging to the field of biomedical materials. The content of β-TCP in the PCL / β-TCP outer layer scaffold is 60%, and the contents of MC and VCM in the PCL / MC / VCM inner layer scaffold are 60% and 5% respectively; the filling density of the PCL / β-TCP outer layer scaffold is 60%, the actual filling wiring distance is 400-500μm, the large pore size is conducive to angiogenesis and bone tissue ingrowth, and the addition of β-TCP improves the osteogenesis of the scaffold. The present invention combines the 3D printing method and the freeze-drying method to construct a composite PT-MCP-V artificial bone scaffold, which has the advantages of a multi-level pore structure, high mechanical strength, and sustained drug release.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a 3D printing construction and preparation method of a vancomycin-loaded multi-level porous artificial bone scaffold model, and specifically to a construction and preparation method of a multi-level porous scaffold artificial bone model prepared by a 3D printed polycaprolactone (PCL) / β-tricalcium phosphate (β-TCP) outer layer porous scaffold and a freeze-drying polycaprolactone (PCL) / mineralized bovine type I collagen (MC) / vancomycin (VCM) inner layer porous scaffold, belonging to the field of biomedical materials. Background Art

[0002] Repair and reconstruction of bone defects is one of the problems faced by orthopedics in clinic. In recent years, due to the rapid development of transportation and industry, bone damage caused by congenital, infectious, tumor and other diseases has been on the rise. Commonly used bone materials in clinic include autologous bone, allogeneic bone and allogeneic bone, but there are still various defects, such as the scarcity of autologous bone and the large bone damage caused during surgery; allogeneic bone has great rejection and is difficult to transplant.

[0003] In order to overcome the problems caused by transplantation, artificial bone materials have always attracted much attention, and the use of artificial bone materials has also been increasing year by year, such as gel, titanium alloy, polymer, calcium sulfate, collagen-based materials, bioactive glass, etc. However, collagen-based materials have good application prospects because collagen is a key component of natural bone tissue, which can promote early mineralization and support the formation of new bone, and the material can be replaced by new bone. Hydroxyapatite is the main inorganic component of natural bone tissue. Using the bionic principle in vitro, a composite with similar composition and hierarchical structure to natural bone can be prepared. Collagen dissolves in an acidic solution, and by adjusting the pH, hydroxyapatite crystals are deposited on the surface of collagen molecules to form mineralized collagen. Good bone repair scaffolds are prepared by combining polymer materials with mineralized collagen, but the mechanical strength of the scaffold is low, the controllability of the pore structure is difficult to adjust, and the range of mechanical strength requirements that can be met for the bone repair site is limited (composite of mineralized collagen and bioceramics and its manufacturing method: CN201210040283.3[P]. 2012-08-15.).

[0004] Polycaprolactone (PCL) is a polymer material approved by the US FDA for clinical use because of its non-toxicity, good biocompatibility, good drug loading performance and degradability, and its degradation products can be metabolized to the outside by the human body. PCL has suitable mechanical strength, but exhibits hydrophobic properties. Combining it with inorganic materials can effectively improve the hydrophobic properties. In addition, combining it with mineralized collagen can effectively improve the problems of low mechanical strength and uncontrollable structure of mineralized collagen alone. In order to achieve good anti-infection performance, VCM can be loaded for sustained drug release to achieve the treatment of local bone infection (Qiu X, Li S, Li X, et al. Experimental study of β-TCP scaffold loaded with VAN / PLGA microspheres in the treatment of infectious bone defects [J]. Colloids and Surfaces B: Biointerfaces, 2022, 213: 112424.). β-tricalcium phosphate (β-TCP), with the chemical formula β-Ca3(PO4)2, belongs to the hexagonal crystal system. β-TCP has excellent mechanical strength, biocompatibility, osteoconduction and osteoinduction (Bohner M, Santoni BLG, Döbelin N. β-tricalcium phosphate for bonesubstitution: Synthesis and properties[J]. Acta biomaterialia, 2020, 113: 23-41.), and is an ideal bioceramic material for bone repair materials. However, due to its low porosity and high brittleness, it is often mixed with high molecular polymers to improve its performance during use.

[0005] Porous scaffolds contain both large pores and micropores, which can promote bone ingrowth. Current studies have shown that macropores are generally considered to be between 100 and 1000 μm in size, which can promote angiogenesis and thus promote bone ingrowth. In addition, the supply of nutrients and removal of metabolic wastes through macropores during in vitro maturation improve the success rate of scaffolds after implantation in vivo. The presence of micropores in macropores, which are generally considered to be between 10 and 100 μm, can promote the increase of capillary forces and the increase of surface area for cell interaction and protein adsorption, leading to physical effects, and the two synergistically promote bone repair (Karageorgiou V, Kaplan D. Porosity of 3D biomaterial scaffolds and osteogenesis [J]. Biomaterials, 2005, 26 (27): 5474-5491.). Fused 3D printing technology (FDM) can meet the requirements of porous scaffolds for macropores. At the same time, due to its personalized characteristics, it has shown great development potential as a technology applied to tissue engineering. Freeze drying is a commonly used technology for manufacturing micropores and is often used in the preparation of bone repair scaffolds. The present invention combines the two technologies to construct a multi-level pore artificial bone scaffold, thereby constructing a scaffold that meets the requirement of micropores in macropores. The two technologies jointly promote bone repair and have great clinical application potential. Summary of the invention

[0006] The present invention provides a 3D printing construction and preparation method of a vancomycin-loaded multi-level porous artificial bone scaffold model. The multi-level porous artificial bone scaffold PT-MCP-V has excellent mechanical strength and drug sustained-release performance, and both the inner and outer layer materials are degradable. After the surface and interior of the bone material are absorbed, bone tissue regeneration can be promoted, and it is finally replaced by autologous bone.

[0007] The present invention provides a vancomycin-loaded multi-level porous artificial bone scaffold model. First, a digital model of a target scaffold is constructed by three-dimensional modeling software; then, a polycaprolactone (PCL) / β-tricalcium phosphate (β-TCP) composite wire is converted from a digital model to a target outer layer porous scaffold by layer-by-layer printing using a 3D printing method to form an interconnected macroporous (400-500 μm) scaffold; in addition, the machine can complete the start → pause → start function through the 3D printer supporting software. Through this operation, the PCL / MC / VCM microporous (10-30 μm) scaffold prepared by freeze drying can be combined with the PCL / β-TCP scaffold to form a PT-MCP-V multi-level porous artificial bone scaffold. The outer layer porous scaffold improves the mechanical strength of the inner layer porous scaffold alone and slows down the drug release rate of the inner layer porous scaffold alone. The inner porous scaffold PCL / MC / VCM contains bovine type I collagen and hydroxyapatite, which simulate the main components of human bones, have good biological activity and can promote bone regeneration and induce osteocyte proliferation after implantation. At the same time, VCM can be locally released at the site of infection to prevent the occurrence of bone infection.

[0008] In the present invention, the outer porous scaffold is prepared by 3D printing with 50-60% mass content of β-TCP composite wire. The addition of β-TCP causes the scaffold to gradually dissolve calcium and phosphorus ions in the body as it degrades, providing raw materials for new tissue to solidify in situ to form new bone. The pore size and porosity can be adjusted by 3D printing, and personalized customized scaffolds can be realized. The inner porous scaffold is prepared by freeze drying with 40-80% weight percentage of MC uniformly dispersed in a polymer PCL solution. At the same time, the inner scaffold is loaded with VCM and implanted into the target site to achieve local drug release, reduce infection and reduce the toxicity of systemic medication. The drug release rate of the single inner PCL / MC / VCM scaffold can be reduced through the action of the outer 3D printed scaffold, so that the drug can be released slowly. The VCM content in the inner scaffold accounts for 5% of the weight of the inner scaffold. The filling density of the PCL / β-TCP outer scaffold is 60%, and the filling wiring distance is 400-500μm.

[0009] The present invention provides a 3D printing construction and preparation method of the above-mentioned vancomycin-loaded multi-level porous artificial bone scaffold, which is characterized by constructing a multi-level porous scaffold model by SolidWorks, 3D printing a PCL / β-TCP outer layer porous scaffold, and freeze-drying to prepare a PCL / MC / VCM inner layer porous scaffold. Specifically, the 3D printing construction method provided by the present invention is:

[0010] In the process of constructing the PT-MCP-V multi-level pore artificial bone scaffold model, 3D printing is used to construct the outer structure and reserve space for the inner scaffold. The steps are as follows:

[0011] (1) Use SolidWorks 3D modeling software to build a hollow cylinder model;

[0012] (2) Use 3D printing slicing software to slice the hollow cylinder and set the printing parameters: layer height is 0.3 mm, printing speed is 30 mm / s, printing temperature is 90 °C, filling density is 60%, and theoretical line spacing is 0.66 mm;

[0013] (3) placing the prepared PCL / β-TCP composite filament into a 3D printer to print the outer layer scaffold;

[0014] (4) When the 3D printer prints to the specified position according to the instructions, the printing is paused and the prepared inner layer PCL / MC / VCM porous scaffold is inserted, and the printing is continued to obtain the PT-MCP-V multi-level porous artificial bone composite scaffold.

[0015] Furthermore, the volume percentage of the inner layer PCL / MC / VCM scaffold to the PT-MCP-V multi-level porous scaffold is 12.4%.

[0016] Furthermore, the above 3D printing construction method is specifically described as follows:

[0017] (1) The filling density of the outer layer 3D printed PCL / β-TCP scaffold is 60%, the theoretical filling line distance is 660μm, the printing speed is 30mm / s, and the actual filling line distance is 400~500μm;

[0018] (2) The PCL / MC / VCM scaffold prepared by inner layer freeze-drying had a pore size of 10-30 μm and a porosity of (57.94±0.50)%; the compression strength of the PCL / MC / VCM (φ 10 mm × H 10 mm) scaffold was (1.16±0.08) MPa, the compression modulus was (1.27±0.06) MPa, and the cumulative drug release percentage over 20 days was (72.19±1.75)%;

[0019] (3) The above inner and outer layer scaffolds were composited to construct a PT-MCP-V multi-level porous artificial bone scaffold, that is, the multi-level porous scaffold model constructed by SolidWorks was used to place the PCL / MC / VCM scaffold into the 3D printed PCL / β-TCP scaffold to compositely construct a PT-MCP-V multi-level porous scaffold, that is, the inner layer was a PCL / MC / VCM scaffold with a pore size of 10~30μm, and the outer layer was a PCL / β-TCP scaffold with a line spacing of 400~500μm. The porosity of the PT-MCP-V (φ 20mm × H 20mm) multi-level porous scaffold was (51.19±0.34)%, which was 7% different from that of the single inner layer scaffold and remained above 50%; the compressive strength was (10.82±0.12) MPa, and the compression modulus was (12.35±0.42) MPa. Compared with the single inner layer scaffold PCL / MC / VCM (φ 10mm × H 10mm), the compressive strength increased by 927% and the compression modulus increased by 966%; the cumulative drug release percentage in 20 days was (70.14±1.94)%.

[0020] Furthermore, SolidWorks modeling software was used to construct a hollow cylinder with outer dimensions of 2x mm in diameter (φ) and 2x mm in height (H) and inner dimensions of x mm in diameter (φ) and x mm in height (H). In order to ensure the accuracy of the 3D printed bracket, 5≤x≤10 was used in the above dimensions.

[0021] When the 3D printer prints to the specified position (i.e., the printing height is 1.5x mm) according to the instruction, the printing is paused and the inner PCL / MC / VCM porous scaffold with a diameter of x mm and a height of x mm is placed in the reserved hole, and then the printing is continued to obtain the PT-MCP-V multi-level porous artificial bone scaffold. The prepared scaffold is sterilized (15kGy of cobalt-60) and stored for later use.

[0022] The present invention provides a method for preparing the above-mentioned PCL / β-TCP composite yarn, which specifically comprises the following steps:

[0023] (1) Preparation of β-TCP by precipitation method: Phosphoric acid and calcium carbonate were added to deionized water at a molar ratio of Ca / P = 0.43 and mixed evenly (the concentration of phosphoric acid was kept at 0.3 M and the concentration of calcium carbonate was kept at 0.13 M). After sufficient reaction for 90 min, a phosphoric acid / calcium carbonate solution was obtained. The phosphoric acid / calcium carbonate solution was slowly dripped into a 0.13 M calcium hydroxide solution using a separatory funnel. The molar ratio of Ca / P in the obtained mixed solution was 0.86. After sufficient reaction for 4 h, calcium carbonate powder was added to the solution so that the molar ratio of Ca / P in the obtained solution was 1.5. After overnight reaction, the precipitate was allowed to stand for 5 h. The precipitate was then centrifuged for 15 min and then ball milled in a ball mill for 2 h. The ball milled product was centrifuged for another 15 min and then placed in a vacuum drying oven at 80 °C for sufficient drying. The dried product was ground and then placed in a muffle furnace for sintering at 1200 °C. The cooled product was ground and passed through a 200-mesh sieve (keeping the particle size below 74 μm) to obtain β-TCP with uniform particle size.

[0024] (2) Preparation of PCL / β-TCP composite yarn: PCL was prepared in 1,4-dioxane at room temperature and stirred thoroughly to maintain a concentration of 10% (w / v); β-TCP was added and stirred continuously to obtain a uniformly mixed PCL / β-TCP solution; the solution was then precipitated in a large amount of water at room temperature to remove the solvent. The precipitate was pre-frozen in a -30℃~-20℃ refrigerator for 2h, and then placed in a -96℃ freeze dryer to further remove organic residues and moisture. The freeze-dried PCL / β-TCP composite material was cut into particles with a diameter of (5±0.5) mm, and the cut PCL / β-TCP particles were heated in a screw extruder at a heating temperature of 70℃ to extrude PCL / β-TCP composite yarns with a diameter of (1.75±0.05) mm.

[0025] The present invention provides a method for preparing the inner layer PCL / MC / VCM porous scaffold, which specifically comprises the following steps:

[0026] (1) Preparation of mineralized bovine type I collagen: bovine type I collagen gel (type I bovine collagen solid content of 1.36%, molecular weight 270-300 KDa) was dissolved in 0.5 M acetic acid solution to prepare a 0.001 g / mL collagen solution. A calcium ion aqueous solution was added to the collagen solution at a rate of 0.12 mol calcium ion / g collagen gel to obtain a calcium / collagen composite solution. A 0.5 M phosphoric acid solution was added dropwise to the obtained calcium / collagen solution at a molar ratio of Ca / P=1.66 to obtain a calcium / phosphorus / collagen composite solution. The mixture was stirred for 2 h. After stirring for 2 hours, adjust the pH value of the calcium / phosphorus / collagen solution to 8, continue stirring for 12 hours, take it out and let it stand for 24 hours, pour out the supernatant to obtain a precipitate, add 5-10 mL of deionized water to the precipitate and repeat centrifugation 5 to 7 times until the pH of the supernatant is 7; pre-freeze the MC at -30℃~-20℃ for 2 hours, and completely dry it in a freeze dryer at -96℃. Grind the freeze-dried MC with a mortar and pass it through a 100-mesh sieve (keep the particle size below 150μm) to obtain MC powder with uniform particle size, which is placed in a 4℃ refrigerator for later use.

[0027] (2) Preparation of inner layer PCL / MC / VCM porous scaffold: Use solvent 1,4-dioxane to dissolve PCL, prepare a PCL solution with a concentration of 0.1g / ml, stir and dissolve at room temperature, add MC and VCM to the completely dissolved PCL solution to obtain a PCL / MC / VCM mixed solution, keep the overall concentration of the solution at 25% (w / v), the mass percentages of MC and VCM in PCL / MC / VCM are 60% and 5%, respectively, and stir thoroughly at room temperature. Then, pour the PCL / MC / VCM mixed solution into a pre-frozen polytetrafluoroethylene mold at room temperature and pre-freeze at -30℃~-20℃ for 2h, then freeze-dry the pre-frozen PCL / MC / VCM scaffold in a -96℃ freeze dryer to remove the organic solvent, and obtain an inner layer PCL / MC / VCM porous scaffold.

[0028] Beneficial effects of the present invention:

[0029] (1) SolidWorks was used to construct a multi-level porous artificial bone scaffold model. The 3D printed PCL / β-TCP outer layer scaffold was composited with the freeze-dried PCL / MC / VCM inner layer scaffold to form a multi-level porous scaffold with different pore sizes in the inner and outer layers, which synergistically promoted bone tissue regeneration.

[0030] (2) The compressive strength of the PT-MCP-V (φ 20 mm × H 20 mm) multi-level pore scaffold was increased from 1.16 MPa to 10.82 MPa compared to the inner layer scaffold of PCL / MC / VCM (φ 10 mm × H 10 mm), making the multi-level pore scaffold conform to a wider range of human cancellous bone mechanics;

[0031] (3) The porosity of the multi-level pore scaffold is maintained above 50%. The addition of the outer layer scaffold reduces the porosity of the PT-MCP-V scaffold, which slows down the drug release rate to a certain extent. The outer layer scaffold has a large pore size of 400-500 μm, and the inner layer has micropores of 10-30 μm, which meets the requirements of porosity and pore size for bone repair;

[0032] (4) Both the inner and outer scaffolds have the effect of promoting the proliferation of MC3T3-E1 (mouse embryonic osteoblast precursor cells) and have good biocompatibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a schematic diagram of the composite construction of the PT-MCP-V multi-level pore artificial bone scaffold of the present invention.

[0034] Figure 2 The microscopic morphologies of PCL / β-TCP composite yarn (a, d), PCL / β-TCP scaffold (b, e) and PCL / MC / VCM (c, f) scaffold in Example 1. a, b, c are low magnifications, and d, e, f are high magnifications.

[0035] Figure 3 Schematic diagram of the antibacterial experiment of PCL / MC / VCM stent in Example 1, without drug loading (a) and with drug loading (b).

[0036] Figure 4 is the release curve of the product; wherein a is the VCM standard release curve, b is the drug release curve of the PT-MCP-V multi-stage porous scaffold in Example 1, and c is the drug release curve of the PT-MCP-V multi-stage porous scaffold in Example 2.

[0037] Figure 5 The porosity of the PCL / MC / VCM scaffold in Example 1 and the PT-MCP-V scaffold in Examples 1 and 2.

[0038] Figure 6 Schematic diagram of stress-strain (a), compressive strength (b) and compression modulus (c) of the PCL / MC / VCM scaffold in Example 1 and the PT-MCP-V scaffold in Examples 1 and 2.

[0039] Figure 7 The CCK-8 assay for cell proliferation in PCL / MC / VCM scaffold and PCL / β-TCP scaffold in Examples 1 and 2 was used. Implementation

[0040] The present invention is further illustrated by the following examples, but is not limited to the following examples. Example

[0041] Preparation of β-TCP by precipitation method: 29.98g phosphoric acid was dissolved in 1000ml pure water, 13.13g calcium carbonate was weighed and evenly added to the phosphoric acid solution, and the reaction was fully reacted for 90min to obtain a phosphoric acid / calcium carbonate solution, 10.13g calcium hydroxide was weighed and dissolved in 1000ml pure water, and the phosphoric acid / calcium carbonate solution was slowly added dropwise to the calcium hydroxide solution using a separatory funnel. After 4h, 13.13g calcium carbonate powder was added to the solution, and the solution was allowed to stand for 5h after overnight reaction. The precipitate was centrifuged for 15min and then placed in a ball mill for 2h. The ball-milled product was centrifuged for 15min and dried in a vacuum drying oven at 80℃ for 24h. The ground and dried precursor was placed in a muffle furnace and sintered at 1200℃ for 5.5h. The cooled product was ground through a 200-mesh sieve (keeping the particle size below 74μm) to obtain β-TCP powder.

[0042] Preparation of PCL / β-TCP composite filaments: PCL was dissolved in 1,4-dioxane at a concentration of 10% (w / v) and stirred at room temperature for 2 h. After adding β-TCP, stirring was continued for 2 h to obtain a uniformly mixed PCL / β-TCP solution. The solution was then precipitated in a large amount of water at room temperature to remove the solvent. The precipitate was pre-frozen in a -30℃~-20℃ refrigerator for 2 h, and then placed in a -96℃ freeze dryer to further remove organic residues and moisture. The freeze-dried PCL / β-TCP composite material was cut into particles with a diameter of about 5 mm, and the cut PCL / β-TCP particles were heated in a screw extruder at a heating temperature of 70℃ to extrude composite filaments with a diameter of (1.75±0.05) mm.

[0043] Preparation of mineralized bovine type I collagen material: 5.51 g of bovine type I collagen gel (type I bovine collagen solid content of 1.36%, molecular weight 270~300KDa) was dissolved in 75 ml of 0.0005 mol / mL acetic acid solution to prepare a 0.001 g / mL collagen solution, and a calcium ion aqueous solution was added to the collagen solution at an amount of 0.12 mol calcium ion / gram collagen gel to obtain a calcium / collagen composite solution, and a phosphate solution was added dropwise to the obtained calcium / collagen solution with Ga / P=1.66 to obtain a calcium / phosphorus / collagen composite solution. After stirring for 2 hours, the pH value of the calcium / phosphorus / collagen solution was adjusted to 8, and stirring was continued for 12 hours. After that, the solution was taken out and allowed to stand for 24 hours, the supernatant was discarded to obtain a precipitate, and the precipitate was added with purified water and centrifuged repeatedly for 7 times until the pH of the supernatant was 7. The mineralized collagen was pre-frozen at -20℃~-30℃ for 2h, and freeze-dried at -96℃ for 24h. The freeze-dried MC was ground with a mortar and passed through a 100-mesh sieve (keeping the particle size below 150μm) to obtain MC powder, which was refrigerated in a 4℃ refrigerator for later use.

[0044] Preparation of PCL / MC / VCM porous scaffolds: Use solvent 1,4-dioxane to dissolve PCL, prepare a PCL solution with a concentration of 0.1g / ml, stir at room temperature for 2h, add MC and VCM to the completely dissolved PCL solution to obtain a PCL / MC / VCM mixed solution, wherein the MC and VCM contents are 60% and 5% of the total weight of the solute, respectively, and stir at room temperature for 1h. Pour the PCL / MC / VCM mixed solution into a pre-frozen polytetrafluoroethylene mold at room temperature and pre-freeze at -30℃~-20℃ for 2h, freeze-dry the pre-frozen PCL / MC / VCM scaffold in a -96℃ freeze dryer to remove the organic solvent, and take it out after 24h to obtain the inner layer PCL / MC / VCM scaffold.

[0045] 3D printed PT-MCP-V multi-level hole bracket: Solid Works modeling software was used to build a hollow cylinder with an outer dimension of φ20mm × H 20mm and an inner dimension of φ10mm × H 10mm. Figure 1 As shown, the outer support is hollow, and the hollow part is used to place the inner support, and the digital model is converted into a physical object through 3D printing.

[0046] The established model was imported into the 3D printing software for slicing. When the 3D printer printed to the specified position (i.e., the printing height of 15 mm) according to the slicing instruction, the printing was paused, and a PCL / MC / VCM porous scaffold with a size of φ 10 mm × H 10 mm was placed. Then, the printing was continued. The prepared PT-MCP-V (φ 20 mm × H 20 mm) multi-level porous scaffold was sterilized (15 kGy of cobalt-60) and set aside.

[0047] like Figure 2 (a) is an electron microscope image of the PCL / β-TCP composite wire. The diameter of the composite wire measured by image j software is 1.73 mm, which is within the error range of (1.75±0.05) mm. Figure 2 (d) is an enlarged image of the composite fiber, and the red arrows point to the β-TCP particles encapsulated in PCL; Figure 2 As shown in (b) and (c), the pore size of the outer PCL / β-TCP scaffold measured by image j software is 433 μm, and the pore size of the inner PCL / MC / VCM scaffold is 10 μm~30 μm. Figure 2 (e, f) are the surface morphologies of PCL / β-TCP scaffold and PCL / MC / VCM scaffold at high magnification;

[0048] Figure 3In order to conduct antibacterial experiments on PCL / MC / VCM (φ 10mm × H 10mm), it can be seen that the inner layer of the stent with added VCM has an obvious inhibition zone. According to the CLSI standard of VCM in the interpretation standard of the inhibition zone diameter for Staphylococcus, the diameter of the inhibition zone of the stent is greater than 15mm, which is in the extremely sensitive range. Example

[0049] The preparation steps of β-TCP, PCL / β-TCP, MC, and PCL / MC / VCM were the same as those in Example 1.

[0050] 3D printed PT-MCP-V multi-stage hole bracket: SolidWorks modeling software was used to construct a hollow cylinder with an outer dimension of φ10mm × H 10mm and an inner dimension of φ 5mm × H 5mm.

[0051] The established model was imported into the 3D printing software for slicing. When the 3D printer printed to the specified position (i.e., the printing height of 7.5 mm) according to the slicing instruction, the printing was paused, and a PCL / MC / VCM porous scaffold with a size of φ 5 mm × H 5 mm was placed, and then the printing was continued. The prepared PT-MCP-V (φ 10 mm × H 10 mm) multi-level porous artificial bone scaffold was sterilized (15 kGy of cobalt-60) and set aside.

[0052] The drug release profile of the stent is shown in Figure 4 ,like Figure 4 (a) shows the standard release curve of VCM drawn by fitting using Origin software before calculating the drug release percentage. The fitting formula is y=-0.01674+5.00357x, R 2 =0.99458. The drug release performance of PCL / MC / VCM stent and PT-MCP-V stent was evaluated by measuring the drug release for 20 days using an experimental UV spectrophotometer.

[0053] Figure 4 (b) is the cumulative drug release percentage data of the PT-MCP-V (φ 20mm × H 20mm) and PCL / MC / VCM (φ 10mm× H 10mm) stents in Example 1 placed in PBS for 20 days. The cumulative drug release percentage of PT-MCP-V within 20 days was (70.1±1.94)%, while the single PCL / MC / VCM stent reached (72.2±1.75)%. At the 6th day of drug release, the difference in the cumulative drug release percentage of the two groups of stents reached a maximum of 10%;

[0054] like Figure 4As shown in (c), the drug release percentage of the PT-MCP-V stent placed in PBS for 8 days was (77.2±1.83)%. The drug release percentage of the PCL / MC / VCM alone (φ 5mm × H 5mm) on the 8th day was (91.9±2.47)%. When the drug was released on the second day, the difference in the cumulative drug release percentage between the two groups of stents reached a maximum of 38%, which greatly slowed down the drug concentration at the target site.

[0055] The porosity of the scaffold is shown in Figure 5 Based on the Archimedean principle, the porosity of the PT-MCP-V (φ 20mm × H 20mm) multi-level pore scaffold in Example 1 was measured by liquid displacement method to be (51.2±0.34)%, which meets the porosity requirements of human bone repair; the porosity of the PT-MCP-V (φ 10mm × H 10mm) in Example 2 was (50.64±0.61)%, which meets the porosity requirements of human bone repair;

[0056] Mechanical properties Figure 6 As shown, Figure 6 The compression curve in (a) shows that the compressive strength of the PT-MCP-V (φ 20mm× H 20mm) and PT-MCP-V (φ 10mm × H 10mm) scaffolds in Examples 1 and 2 is significantly improved compared to the compressive strength of the PCL / MC / VCM (φ 10mm× H 10mm) scaffold, while the PCL / MC / VCM (φ 10mm × H 10mm) scaffold is structurally destroyed at a strain of 0.5 and cannot be further compressed, and the resulting compressive strength cannot meet the mechanical requirements of human bone repair.

[0057] Figure 6 (b) (c) reflect the mechanical properties of the scaffold. Through testing: in Example 1, the compressive strength of PT-MCP-V (φ 20mm × H20mm) can reach (10.8±0.12) MPa, and the compression modulus is (12.35±0.42) MPa. Compared with the single PCL / MC / VCM (φ 10mm × H 10mm), the compression strength is increased by 927%, and the compression modulus is increased by 966%; in Example 2, the compressive strength of PT-MCP-V (φ 10mm × H 10mm) can reach (9.0±0.33) MPa, and the compression modulus is (7.7±0.40) MPa. Compared with the PCL / MC / VCM (φ 10mm × H 10mm) scaffold, the compression strength is increased by 774%, and the compression modulus is increased by 608%;

[0058] CCK-8 test results are shown in Figure 7, the absorbance of the scaffold continued to increase with the extension of culture time, indicating that the scaffold can promote the proliferation of MC3T3-E1 (mouse embryonic osteoblast precursor cells) and has good biological activity.

[0059] The multi-level pore artificial bone scaffold constructed by the present invention through 3D printing and freeze drying is in line with the mechanics of human cancellous bone; the porosity of the multi-level pore artificial bone scaffold is greater than 50%, which meets the porosity requirements of bone repair; the construction of the multi-level pore artificial bone scaffold effectively slows down the drug release rate of the inner scaffold; cells have significantly proliferated on both the inner and outer scaffolds, and have good biocompatibility. In the personalized bone repair stage, the porosity, printing aperture and mechanical strength of the multi-level pore scaffold can be adjusted by adjusting the filling rate of 3D printing, so as to prepare an artificial bone scaffold that meets clinical needs, which has broad clinical application prospects.

Claims

1. A vancomycin-loaded multi-level porous artificial bone scaffold model, characterized in that: SolidWorks was used to construct a multi-level porous artificial bone scaffold model. The 3D printed PCL / β-TCP outer scaffold was composited with the freeze-dried PCL / MC / VCM inner scaffold to form a multi-level porous scaffold with different pore sizes in the inner and outer layers. The outer layer scaffold contains 50-60% by weight of β-TCP composite filaments. The addition of β-TCP causes the scaffold to gradually dissolve calcium and phosphorus ions as it degrades in the body, providing raw materials for new tissues to solidify in situ to form new bones. The inner layer scaffold is made by freeze-drying 40-80% by weight of MC uniformly dispersed in a polymer PCL solution, and the inner layer scaffold is loaded with VCM, and the VCM content in the inner layer scaffold accounts for 5% of the weight of the inner layer scaffold. The 3D printing construction and preparation method of the vancomycin-loaded multi-level porous artificial bone scaffold model is as follows: in the process of constructing the PT-MCP-V multi-level porous artificial bone scaffold model, the outer layer structure is constructed by 3D printing and the space of the inner layer scaffold is reserved, and the steps are as follows: (1) Use SolidWorks 3D modeling software to build a hollow cylinder model; (2) Use 3D printing slicing software to slice the hollow cylinder; (3) The prepared PCL / β-TCP composite filament was placed in a 3D printer to print the outer layer bracket; the printing parameters were: layer height of 0.3 mm, printing speed of 30 mm / s, printing temperature of 90 °C, filling density of 60%, and actual filling line distance of 400-500 μm; (4) When the 3D printer prints to the specified position according to the instruction, the printing is paused and the prepared inner layer PCL / MC / VCM porous scaffold is placed, and the printing is continued to obtain the PT-MCP-V multi-level porous artificial bone scaffold; The porosity of the obtained PT-MCP-V multi-level porous artificial bone scaffold was (51.19±0.34)%, which was maintained above 50%; the compressive strength was (10.82±0.12) MPa, and the compression modulus was (12.35±0.42) MPa; the cumulative drug release percentage in 20 days was (70.14±1.94)%; The volume percentage of the inner layer PCL / MC / VCM porous scaffold to the PT-MCP-V multi-level porous artificial bone scaffold is 12.4%.

2. A 3D printing construction and preparation method of the vancomycin-loaded multi-level porous artificial bone scaffold model according to claim 1, characterized in that: In the process of constructing the PT-MCP-V multi-level pore artificial bone scaffold model, 3D printing is used to construct the outer structure and reserve space for the inner scaffold. The steps are as follows: (1) Use SolidWorks 3D modeling software to build a hollow cylinder model; (2) Use 3D printing slicing software to slice the hollow cylinder; (3) The prepared PCL / β-TCP composite filament was placed in a 3D printer to print the outer layer bracket; the printing parameters were: layer height of 0.3 mm, printing speed of 30 mm / s, printing temperature of 90 °C, filling density of 60%, and actual filling line distance of 400-500 μm; (4) When the 3D printer prints to the specified position according to the instructions, the printing is paused and the prepared inner layer PCL / MC / VCM porous scaffold is inserted, and the printing is continued to obtain the PT-MCP-V multi-level porous artificial bone scaffold.

3. The 3D printing construction and preparation method of the vancomycin-loaded multi-level porous artificial bone scaffold model according to claim 2, characterized in that: The PCL / MC / VCM scaffolds prepared by inner layer freeze-drying had a pore size of 10-30 μm and a porosity of (57.94±0.50)%; the compression strength of the PCL / MC / VCM scaffolds was (1.16±0.08) MPa, the compression modulus was (1.27±0.06) MPa, and the cumulative drug release percentage in 20 days was (72.19±1.75)%.

4. The 3D printing construction and preparation method of the vancomycin-loaded multi-level porous artificial bone scaffold model according to claim 2, characterized in that: The preparation method of PCL / β-TCP composite yarn comprises the following steps: (1) Preparation of β-TCP by precipitation method: Phosphoric acid and calcium carbonate were added to deionized water at a molar ratio of Ca / P = 0.43 and mixed evenly. The concentration of phosphoric acid in the solution was 0.3 M and the concentration of calcium carbonate was 0.13 M. After sufficient reaction for 90 min, a phosphoric acid / calcium carbonate solution was obtained. The phosphoric acid / calcium carbonate solution was slowly dripped into a 0.13 M calcium hydroxide solution using a separatory funnel. The molar ratio of Ca / P in the obtained mixed solution was 0.

86. After sufficient reaction for 4 h, calcium carbonate powder was added to the solution so that the molar ratio of Ca / P in the obtained solution was 1.

5. After overnight reaction, the solution was allowed to stand for 5 h. The precipitate was then centrifuged for 15 min and then ball milled in a ball mill for 2 h. The ball milled product was centrifuged for another 15 min and then placed in a vacuum drying oven at 80 °C for sufficient drying. The dried product was ground and then placed in a muffle furnace for sintering at 1200 °C. The cooled product was ground and passed through a 200-mesh sieve to obtain β-TCP with uniform particle size. (2) Preparation of PCL / β-TCP composite filaments: PCL was prepared in 1,4-dioxane at room temperature and stirred thoroughly to maintain a mass volume concentration of 10%; β-TCP was added and stirred continuously to obtain a uniformly mixed PCL / β-TCP solution; the solution was then precipitated in a large amount of water at room temperature to remove the solvent; the precipitate was pre-frozen in a -30℃~-20℃ refrigerator for 2 h, and then placed in a -96℃ freeze dryer to further remove organic residues and moisture; the freeze-dried PCL / β-TCP composite material was cut into particles with a diameter of (5±0.5) mm, and the cut PCL / β-TCP particles were heated in a screw extruder at 70℃ to extrude PCL / β-TCP composite filaments with a diameter of (1.75±0.05) mm.

5. The 3D printing construction and preparation method of the vancomycin-loaded multi-level porous artificial bone scaffold model according to claim 2, characterized in that: The preparation method of the inner layer PCL / MC / VCM porous scaffold comprises the following steps: (1) Preparation of mineralized bovine type I collagen: Bovine type I collagen gel was dissolved in 0.5 M acetic acid solution to prepare a 0.001 g / mL collagen solution. A calcium ion aqueous solution was added to the collagen solution at a molar ratio of 0.12 mol calcium ion / g collagen gel to obtain a calcium / collagen composite solution. A 0.5 M phosphoric acid solution was added dropwise to the obtained calcium / collagen solution at a molar ratio of Ca / P=1.66 to obtain a calcium / phosphorus / collagen composite solution. After stirring for 2 h, the calcium / phosphorus / collagen composite solution was added. The pH value of the phosphorus / collagen solution was adjusted to maintain at 8, and the solution was taken out and allowed to stand for 24 hours after continued stirring for 12 hours. The supernatant was discarded to obtain a precipitate. The precipitate was added with 5-10 mL of deionized water and centrifuged repeatedly for 5-7 times until the pH value of the supernatant was 7. The MC was pre-frozen at -30°C to -20°C for 2 hours, and completely dried in a freeze dryer at -96°C. The freeze-dried MC was ground with a mortar and passed through a 100-mesh sieve to obtain MC powder with uniform particle size, which was placed in a refrigerator at 4°C for later use. (2) Preparation of inner layer PCL / MC / VCM porous scaffold: Use solvent 1,4-dioxane to dissolve PCL, prepare a PCL solution with a concentration of 0.1 g / ml, stir and dissolve at room temperature, add MC and VCM to the completely dissolved PCL solution to obtain a PCL / MC / VCM mixed solution, maintain the solution mass volume concentration at 25%, and stir thoroughly at room temperature; then, pour the PCL / MC / VCM mixed solution into a pre-frozen polytetrafluoroethylene mold at room temperature and pre-freeze at -30℃~-20℃ for 2h, freeze-dry the pre-frozen PCL / MC / VCM scaffold in a -96℃ freeze dryer to remove the organic solvent, and obtain an inner layer PCL / MC / VCM porous scaffold.

6. The 3D printing construction and preparation method of the vancomycin-loaded multi-level porous artificial bone scaffold model according to claim 5, characterized in that: The solid content of type I bovine collagen in the bovine type I collagen gel is 1.36%, and the molecular weight is 270~300kDa.

Citation Information

Patent Citations

  • Mineralized collagen / bioceramic composite and manufacturing method thereof

    CN102631702A

  • Silk fibroin / polymer-based tubular stent with three-dimensional ordered and disordered double network structures and preparation and usage methods thereof

    CN110215540A

  • Medical implant, particularly orbital implant with repeated administration and drug sustained-release effect

    CN111110396A

  • Bi-layered bone-like scaffolds

    US20110313538A1